Pengaruh Subtitusi Tepung Kedelai Dalam Ransum Basal Dengan Tepung Daun Kelor Terfermentasi Terhadap Performance Ayam Broiler Fase Grower - Bhae, Christianus Yoseph Ngiso; Sago, Yohanes; Betu, Silverius (CV. SINAR HOWUHOWU, 2026)
One practical solution to several poultry problems, particularly those related to feed, is to utilize local resources. One example is the use of moringa leaf flour as a vegetable protein feed ingredient. Moringa leaf supplementation is believed to impact chicken immunity, health, and productivity (Mahfuz and Pio, 2019). This study aimed to determine the effect of substituting soybean flour with fermented moringa leaf flour on the performance of broiler chickens in the grower phase. The study was conducted using a completely randomized design consisting of four treatments and four replications. Treatment P0 = 100% Basal Ration (16% Soybean Flour), P1 = 100% Basal Ration (10% Soybean Flour + 6% Fermented DOC), P2 = 100% Basal Ration (5% Soybean Flour + 11% Fermented DOC), P3 = 100% Basal Ration (16% Fermented DOC). Based on the ANOVA analysis test and Duncan's further test, it shows that the effect of substituting soybean flour with fermented moringa leaf flour on the performance of broiler chickens in the grower phase has a very significant effect on feed consumption (P <0.01), has a significant effect on body weight gain (P <0.05), and has a significant effect on feed conversion. Based on the results of the study, it can be concluded that the effect of substituting soybean flour with fermented moringa leaf flour on the performance of broiler chickens in the grower phase has a significant effect on the performance of broiler chickens.